James Herriot's treasury for children - Herriot, James; Barrett, Peter; Brown, Ruth (St. Martin's Press New York, 1992)
A collection of the author's stories for children, including "Moses the Kitten", "the market square dog, " and "Smudge, the Little lost lamb"
Moses the Kitten - Only one Woof - The Christmas day Kitten - Bonny's big day - Blossom Comes home - The Market square dog - Oscar, cat about town - Smudge, the little lost lamb
4 - 8 years
Keywords: Pets -- England - Yorkshire -- Juvenile literature; Domestic animals -- England - Yorkshire -- Juvenile literature; Farm life -- England - Yorkshire